Molecular dynamics in solid bis(eta-arene)molybdenum complexes studied by solid-state deuterium nuclear magnetic resonance spectroscopy - OHare, D; Heyes, S; Barlow, S; Mason, S (1996)
Variable-temperature solid-state 2H NMR spectra have been recorded on microcrystalline samples of [Mo(η-C6D6)2], [Mo{η-C6D3(CD3)3-1,3,5} 2] and [ZrS2{Mo[η-C6D3(CD3) 3-1,3,5]2}0.15]. In the case of [Mo(η-C6D6)2] the spectra are invariant in the range 160-360 K and are consistent with rapid ring rotation at all accessible temperatures. For both [Mo{η-C6D3(CD3)3-1,3,5} 2] and [ZrS2{Mo[η-C6D3(CD3) 3-1,3,5]2}0.15] the η-C6D3(CD3)3 ligands were found to be static at all temperatures up to 360 K.